The Postoperative Meniscus: Anatomical, Operative, and Imaging Considerations - Cordle, Andrew C.; Williams, Don D.; Andrews, Carol L. (Seminars in Musculoskeletal Radiology, 2018)
Meniscal surgery is commonplace. Patients who have had prior surgery may return for additional imaging for continued or new pain, limited range of motion, or interval injury. Accurate interpretation of postoperative imaging requires a clear understanding of the normal meniscal anatomy and biomechanics. Surgical goals and current surgical techniques impact the imaging appearance. These techniques are reviewed in the context of the various meniscal tear patterns. Multiple imaging modalities may be used in patient assessment with magnetic resonance (MR) imaging providing key information regarding the integrity of the meniscal repair. Imagers need to be aware of the key findings for a normal versus pathologic appearance to the postoperative meniscus as well as other potential MR findings that may account for patient presentation.
Keywords: postoperative meniscus; partial meniscectomy; meniscal repair; magnetic resonance imaging; magnetic resonance arthrography